Magnetic moment and spin state transition on rare monovalent iron ion in nitridoferrate Ca6Li0.5Fe0.5Te2N3. Issue 3 (5th January 2017) - Yan, Xun-Wang; Huang, Zhongbing; Zhang, Chunfang; Gao, Miao; Chen, Lei; Zhong, Guohua; Lin, Hai-Qing
Abstract : Spin state transition on rare monovalent iron ions in linear N–Fe–N chain in nitridoferrate Ca6 Li0.5 Fe0.5 Te2 N3 . Abstract : By first principles simulation, we studied the magnetic properties of Ca6 (Li0.5 Fe0.5 )Te2 N3 including the spin moment, orbital moment, and pressure-driven spin state transition of Fe ion from the high-spin ( S = 3/2) to the low-spin ( S = 1/2) state. Our spin-polarized calculations have correctly revealed that Ca6 (Li0.5 Fe0.5 )Te2 N3 is a magnetic semiconductor with a band gap of 0.49 eV. The spin moment around the Fe ion with a 3d 7 configuration is 3.0 μ B, and the orbital moment is 0.15 μ B, which is contrary to the large orbital moment suggested by experiment. With increasing pressure, a high-spin to low-spin state transition with an Fe moment collapse from 3 μ B to 1 μ B occurs at 18 GPa, accompanied by a semiconductor to metal transition. The underlying mechanism is explained in terms of the interplay between the crystal field and the electron population of the Fe 3d orbitals.